2017
DOI: 10.1186/s40779-017-0123-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological screenings for infection control in unaccompanied minor refugees: the German Armed Forces Medical Service’s experience

Abstract: BackgroundThe German Military Medical Service contributed to the medical screening of unaccompanied minor refugees (UMRs) coming to Germany in 2014 and 2015. In this study, a broad range of diagnostic procedures was applied to identify microorganisms with clinical or public health significance. Previously, those tests had only been used to screen soldiers returning from tropical deployments. This instance is the first time the approach has been studied in a humanitarian context.MethodsThe offered screenings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
2
13
3
1
Order By: Relevance
“…Helminthic infections can also potentially cause serious health consequences for infected individuals, however, person-to-person transmission does not represent an issue and treatment is comparatively straight forward. Like our study, other studies reported high prevalence of some helminths targeted by the screening of asymptomatic individuals [ 14 , 25 ]. While the implementation of screening activities for these infections sometimes faces obstacles, such as refusal to supply biological samples and test limitations (low sensitivity of stool examination in case of Schistosoma spp.…”
Section: Discussionsupporting
confidence: 81%
“…Helminthic infections can also potentially cause serious health consequences for infected individuals, however, person-to-person transmission does not represent an issue and treatment is comparatively straight forward. Like our study, other studies reported high prevalence of some helminths targeted by the screening of asymptomatic individuals [ 14 , 25 ]. While the implementation of screening activities for these infections sometimes faces obstacles, such as refusal to supply biological samples and test limitations (low sensitivity of stool examination in case of Schistosoma spp.…”
Section: Discussionsupporting
confidence: 81%
“…The observed HBsAg seroprevalence of 1.4% was lower as compared to majority of previous studies among asylum seeker in Europe [ 17 , 18 , 20 , 25 – 28 , 31 ]. A hepatitis B seroprevalence study among adult asylum seekers from Middle-East and Horn of Africa in the Netherlands in 2016 concluded a lower HBsAg prevalence of approximately 1% as compared to our study [ 32 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore a high overall morbidity of 87.7% with at least one clinical diagnosis or suspicious laboratory result was seen in this cohort, which is relatively high compared to data from Berlin where 56.6% had no pathological finding [ 22 ]. A study on microbiological screening in Hamburg, Germany found pathogenic and non-pathogenic microorganisms in apparently healthy URM [ 23 ], while in Western Australia over 90% of the participants in a voluntary health assessment were referred to special, multidisciplinary paediatric health clinics [ 24 ]. The majority of the resulting health care needs in this refugee population are known to general practitioners in Germany.…”
Section: Discussionmentioning
confidence: 99%